THE USE DUOLINGO AS A TECHNOLOGY-BASED LEARNING MEDIA IN GRADE 5 ELEMENTARY SCHOOLS (Journal of English Language Teaching and Education (JELTE), 2023)
This study examines perceptions of Duolingo as a tool for learning English. In this study, an experimental sample was taken from 5th grade elementary school, using the pre-test and post-test groups in the study. The researcher found that the students had difficulties in mastering English vocabulary. Some of the factors include, the lack of teacher motivation in developing class vocabulary and mastering student vocabulary, the teacher only takes vocabulary from books, English is not a compulsory subject so there are only 2 (two) hours a week and the tendency for children to be older to play. Based on the problems above, the researchers interes t in choosing the Duolingo application is that the application uses game techniques that make its use easy and fun. Gamification is a game-based learning and aesthetic mechanism that stimulates people to think, play, motivate and solve problems (Kapp, 2012). This study found that the Duolingo app can be used as a teaching tool to improve students skills. in grade 5 elementary school in class to improve their English. This means that the hypothesis is accepted and Duolingo can be used to expand vocabulary. The researcher recommends that English teachers use the Duolingo application to teach English vocabulary, because this application can stimulate students interest in learning processes and activities .